Some problems in the pursuit of social development in the Philippines - Cariño, Ledivina V. (Philippine Journal of Public Administration, 1978)
Although the Philippine Development Plan placed the emphasis on social rather than economic goals, the struggle for priority between the two is a continuing one. An analysis of two cases - the Philippine Sinter Corporation and a proposed copper smelter plant- suggests that as long as an economic calculus is used, the structural causes of community problems are ignored, and negative social consequences are dismissed as a "local"problem, social development would be difficult to attain.